(untitled) (Iraqi Journal of Medical Sciences, 2022)
Background: Insulin resistance is a major risk factor in the development of cardiovascular diseases and type 2 diabetes mellitus. Some studies concluded that serum lipoproteins levels and hence lipoprotein ratios were altered in patients with insulin resistance. Objective: To identify the possibility of using lipoprotein ratios as markers for insulin resistance. Methods: A cross sectional study conducted in Baghdad (Medical City) and in Maysan (Al Shaheed Al Sadir Teaching Hospital) from February to December 2020. Eighty-three male and 51 female in Coronary Care Unit and Internal Medicine Wards patients were selected in the study group. Results: Lipoprotein ratios were significantly higher in individuals with homeostatic model assessment for insulin resistance (HOMA-IR) ?2.5 as compared to subjects with HOMA-IR